Analysis of Stabilization of Price Fixing for Foreign and Domestic Tourists in the Perspective of Islamic Business Ethics - Rojabi Azharghany; Sitti Suryaningsih (Institute of Computer Science (IOCS), 2021)
Currently, buying and selling activities have developed very rapidly, this is due to the development of technology and the level of creativity of the nation's children. Along with the development of the times, selling and buying activities can also be done quickly, namely by making transactions through several applications on mobile phones or what we usually call an online shop. However, not many people ignore offline buying and selling, because business people will always come up with the latest innovations to attract the attention of buyers. All of that can be proven, one of which is the development of modern markets such as hypermart, alfamart, carrefour and many others that have spread widely in various cities in Indonesia. To realize an ideal market, it must be supported by two factors. First, competitive prices on the second trade commodity, the absence of imperfect competition, monopoly, oligopoly or cartel in certain commodities. The data obtained is by field research (field research). The data collection methods are observation, interview or interview and documentation. Business actors must be careful in determining the price to be marketed, therefore it is necessary to formulate an appropriate strategy in the product pricing system, to increase profits and the level of consumer satisfaction. Mistakes in pricing can have various consequences for the company, such as reduced levels of consumer satisfaction and trust, so that buyers feel uncomfortable and will switch to looking for other business actors. In addition, buyers can also make a rejection reaction and it will even be fatal with an action that can drop the company's good name. Whereas in Islamic business ethics, price fixing must be applied fairly and without disadvantage between the seller and the buyer.